2017
DOI: 10.21608/bvmj.2017.30006
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of new nanocomposite natural product (basic nano-curcumin) against breast carcinoma

Abstract: Present study focused on evaluation of the effect of national nancomposite product on serum biochemical profile and programmed cell death (apoptosis) by using Annexin V-FITC and PI test of breast carcinoma female rats. Basic nanocurcumin was tested for its protective effect on breast cancer female rats (n= 30) divided in two main groups (NTBR) and (TBR) which in turn classified into (TBR-Control Positive and TBR-basic nano-curcumin protective groups). Basic nano-curcumin was formulated and tested for both IC50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Furthermore, the biocompatibility effect of water-soluble nanocurcumin overcomes the cytotoxic effect gained from dissolving curcumin in organic solvents. The results of previous studies have confirmed the prompt cytotoxicity of nanocurcumin against different cancer cells with reduced IC 50 values [ 46 – 48 ]. Moreover, combining nanocurcumin with berberine has receded the IC 50 of the latter, displaying a synergistic anticancer efficacy in fighting breast cancer cells [ 49 ].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Furthermore, the biocompatibility effect of water-soluble nanocurcumin overcomes the cytotoxic effect gained from dissolving curcumin in organic solvents. The results of previous studies have confirmed the prompt cytotoxicity of nanocurcumin against different cancer cells with reduced IC 50 values [ 46 – 48 ]. Moreover, combining nanocurcumin with berberine has receded the IC 50 of the latter, displaying a synergistic anticancer efficacy in fighting breast cancer cells [ 49 ].…”
Section: Discussionsupporting
confidence: 63%
“…This concept has been invested in using nanocurcumin as a natural chemo-preventive candidate against the development of breast cancer in a mammary carcinogenesis model. The rats co-treated with nanocurcumin during cancer induction have shown resistance to developing cancer with pronounced apoptotic tissue reaction [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to its low bioavailability, the benefits are not utilized efficiently in the tumor site, and thus the importance of nanocurcumin is more focused due to its ability to enhance the benefits of curcumin as it increases the binding of the phytoconstituents in the target site and helps in treating the tumors [ 108 ]. The effect of nanocurcumin on breast cancer cell lines was investigated, and it was deduced that nanocurcumin was found to be an effective anti-tumor agent along with low toxicity [ 109 ]. Moreover, ref.…”
Section: Uses Of Nanocurcuminmentioning
confidence: 99%
“…Cur has also been approved by the FDA and has a therapeutic effect against a variety of diseases. It has not only a chemotherapeutic effect but also a chemo-preventive effect against certain types of cancer (Abou Zaid et al 2017). The low solubility of Cur decreases its therapeutic effect (Baek and Cho 2017), so the formation of Cur NPs has enhanced the bioavailability and the targeting of cancer cells (Sonekar et al 2016).…”
Section: Introductionmentioning
confidence: 99%